Pengaruh Keberadaan Agrowisata Taman Air Percut Terhadap Sosial Ekonomi Masyarakat (Studi Kasus: Desa Tanjung Selamat, Kec. Percut Sei Tuan, Sumatera Utara) - Azwana Azwana; Yusniar Lubis; Indah Dewi Permata (Mahesa Research Institute, 2023)
This study aims to determine the effect of the existence of Percut Air Park agrotourism on the socio-economic community in Tanjung Selamat Village, Percut Sei Tuan District, Kab. Deli Serdang, North Sumatra. The sample in this study was the community of Tanjung Selamat Village with a total sample of 75 respondents. The data collected are primary data and secondary data. The analytical method used is simple linear regression. The results showed that the existence of Percut Air Park agro-tourism had a positive effect on the socio-economic community of Tanjung Selamat Village. The development of the Percut Air Park agro-tourism area improves the socio-economic conditions of the surrounding community. This can be seen from the emergence of business opportunities, employment, and increased income of the surrounding community. However, the existence of Percut Air Park Agrotourism does not affect the Socio-Cultural of the local community. The community still carried out social and religious activities before and after the Percut Air Park agro-tourism.